Dari Konflik Menuju Penanganan Sampah Plastik: Ma’na Cum Maghza QS. Al-Rum: 41 Tentang Kerusakan Laut - Zulfi Fadhlurrahman; Zaeni Anwar; Muhammad Ikbal Amsah; Tri Nurcahyani Sari Tanjung; Nailul Khoiril Marom (Al-Bayan: Jurnal Studi Al-Qur'an dan Tafsir, 2025)
The problem of plastic waste in the ocean is currently an important concern because of its great impact on the environment and human life. This research departs from the concern that the study of Qur'an interpretation is still rarely directly associated with modern environmental issues, especially about marine pollution. The purpose of this research is to understand the message of QS. Al-Rum: 41 about damage at sea using ma‘nā-cum-maghzā approach which emphasizes the meaning and moral message of the verse in the contemporary context. This research uses a qualitative method with a descriptive-analytical approach through a literature review, which explores various classical and contemporary interpretations. The results of the study show that the verse not only talks about the consequences of human actions in general, but also contains a moral message for humans to maintain the balance of nature and not damage it, including the sea which is now polluted with plastic waste. In conclusion, ma‘nā-cum-maghzā approach helps to relate the values of the Qur'an to today's environmental issues in terms of environmental damage caused by plastic waste, so that the interpretation becomes more relevant and solutive. Academically, this research contributes to the development of a more contextual thematic interpretation and encourages ecological awareness in an Islamic perspective.